The individualization of political activism: A reflection on social movements and modernization, starting from the case of Italian animal advocacy. Issue 3 (2nd March 2020) - Bertuzzi, Niccolò
Abstract : Purpose: The study aims to investigate a relevant topic, but still underestimated by sociological studies: animal advocacy, namely, the organized interest in non-human animals' life, rights and well-being. The Italian case is discussed, with a twofold objective: to highlight the evolution of some repertoires of contention and to use this study to analyze the changes of contemporary collective mobilizations and their relation with the modernization process. Design/methodology/approach: The analysis is based on an online survey (704 responses nationwide), 24 semi-structured interviews with relevant members of groups and associations and a protest event analysis. Furthermore, a vast empirical archive and some academic studies concerning Italian animal advocacy in its historical dimension have been consulted. Findings: The paper underlines the current specificities of Italian animal advocacy, compared to past decades. The great importance assumed by personal action frames and repertoires of contention emerged as characterizing elements. Activism is always more individual and less related to collective organizations: the central role of veganism and of the internet as protest tool is underlined. Both the increasing possibilities offered by better discursive opportunities structure, but also the possible incorporation of more radical frames within consumer market dynamics emerged from the interviews and the survey. Originality/value: The phenomenon of animal advocacy (and, more generally, the activities of contemporary social movements) is contextualized within some typical characteristics of modernity, looking both at structural "opportunities" (e.g.: the diffusion of post-materialist values) and "constraints" (e.g.: veganwashing operations). Based on previous definitions coming from social movements studies and following a debate hosted by this journal, the role of collective organizations and especially the centrality assumed by individual activism is critically analyzed, evaluating the new possibilities, but also the possible negative sides. Not only cultural changes, but also political and legal contexts matter. In this sense, both a focus on Italy and more general reflections on western modernities are proposed, trying to go beyond animal advocacy and reflecting on social movements and collective mobilizations more widely.